Hipomineralización en incisivos y molares permanentes según género y factores de riesgo en pacientes de 6 a 11 años del CEIPSMP "Sagrada Familia" - Monteiro Garcia, Harold Luigi (2023)
OBJECTIVE: To establish the relationship between molar incisor hypomineralization (MIH) and gender, and severity with risk factors in children from 6 to 11 years of age at CEIPSM "Sagrada Familia" METHOD: A quantitative research was developed. Non-experimental, crosssectional and correlational design. Made up of 455 student children from 6 to 11 years of age from CEIPSM “SAGRADA FAMILIA”. For the diagnosis, the criteria established by the European Academy of Pediatric Dentistry (EAPD) were used, for the degree of severity the Mathu-Muju and Wright criteria were used. Schoolchildren who presented this condition were given a survey to parents with risk factors linked to the appearance of MIH. RESULTS: In relation to the prevalence, the sample presented 15% of cases MIH in relation to gender, the female showed 53% of cases of MIH compared to the male sex with 47%. Regarding age, a higher percentage was shown for 9-yearold schoolchildren with 19.7%. The Highest percentage in the degree of severity was mild with 80.3%. The MIH presented a higher percentage in both jaws and on both sides, both right and left. The risk factors present in schoolchildren with MIH were found in a higher percentage in the prenatal stage to Hypocalcemia 24.2%, in the perinatal factors to delivery by cesarean section with 34.8% and in the postnatal factors to the consumption of Antibiotics with 83.3%, finally a relationship was found between the degree of severity with age, the jawbone and the presence of Hypoavitaminosis and Varicella/Measles. CONCLUSIONS: MIH was not related to gender, a relationship of severity was found with the proposed risk factors, Schoolchildren who presented mild severity require a timely visit to their dentist for the corresponding preventive treatments avoiding hypersensitivity, those of moderate to severe degree a restorative treatment, to prevent post-eruptive fractures and a rapid progression of caries.